Staying or Leaving? The Influence of Employees’ Engagement towards Turnover Decision Among Employees of A Semi-Government Organization in Malaysia - Akhir, Romiza Md; Ahmad, Siti Nor Bayaah; Ahmad, Huwaina; Hashim, Nor Azira (American Journal of Social Sciences and Humanities, 2018)
The success or failure of an organization is relevantly depending on its employees’ turnover decision. Employee engagement is one of the factors, which may contribute towards the human resource seasoned issue. This study stands with the purpose to examine the effect of employee engagement towards the staying decision among the employees of Selangor State Economic Development Corporation or Perbadanan Kemajuan Negeri Selangor (PKNS). PKNS is a semi-government organization where its core business is property development. A quantitative experimental design has been conducted to analyze the relationship between independent and dependent variables. Non-probability sampling designs using convenient sampling were run among 250 PKNS employees. Previous literature from EBSCO, Proquest, and Emerald online databases were referred as secondary data. Data analysis was conducted by using the Statistical Package for the Social Science (SPSS). It accepted the hypothesis developed during the study. Employee engagement was discovered to have a significant relationship with employees’ intention to stay.